Pendidikan akhlak anak fase Tamyiz usia 7-10 Tahun - Rahayu, Anissa Maila; Mujahidin, Endin; Rahman, Imas Kania (Tawazun: Jurnal Pendidikan Islam, 2023)
Education is a human endeavor in an effort to improve the personality through all of the potential development that is possessed in the intellectual, physical, and spiritual aspects. The foundation of children's noble characters needs to be formed seriously from an early age because educating characters from an early stage could stimulate the optimization of the various aspects of development which will give a huge impact on their demeanor in the future. In the phase of tamyiz, children must be prepared to receive mukallaf status, which means that the mandate of Abdullah must be completely understood and applied in the form of worship. The purpose of this research is to systematize the character education of the tamyiz phase aged 7-10 years old in the form of an educational curriculum. This research used a library study approach. The results are (1) the purpose of character education is to instill goodness and justice in oneself as a servant of Allah SWT. and social beings, (2) the character education's programs are focused on faith, Islam, and Ihsan (belief, shari'a, and characters), (3) the character education's methods are adapted to the material, including the process of exemplary, example, involvement, strengthening, togetherness, and talk about it, and (4) evaluation of character education can use measurements and assessments that have many varieties, but the benchmark is not just a number but the closeness to Allah SWT. It becomes an inevitability if the basics of children's character education are fulfilled, then it will manifest a noble human being who will get the blessing of Allah SWT insyaa Allah. Abstrak Pendidikan merupakan usaha manusia dalam upaya meningkatkan kepribadiannya melalui pembinaan segala potensi yang dimiliki pada aspek akal, jasmani, dan rohani. Fondasi akhlak mulia anak perlu dibentuk dengan serius sejak dini sebab mendidik akhlak dalam periode pertumbuhan dapat merangsang optimalisasi perkembangan berbagai aspek diri yang akan berdampak pada sikapnya di masa mendatang. Pada fase tamyiz, anak harus dipersiapkan untuk menyambut status mukalaf yang berarti amanah abdulah harus tuntas dipahami sehingga berwujud peribadahan. Tujuan penelitian ini adalah untuk menyistemisasikan pendidikan akhlak anak fase tamyiz usia 7-10 tahun dalam bentuk kurikulum pendidikan. Penelitian ini menggunakan pendekatan kepustakaan (library research). Hasil dari penelitian adalah (1) tujuan pendidikan akhlak untuk menanamkan kebaikan dan keadilan dalam diri sebagai hamba Allah Swt. dan makhluk sosial, (2) program pendidikan akhlak difokuskan tentang iman, Islam, dan ihsan (akidah, syariat, dan akhlak), (3) metode pendidikan akhlak disesuaikan dengan materi, meliputi proses peneladanan, pencontohan, keterlibatan, penguatan, kebersamaan, dan membicarakannya, dan (4) evaluasi pendidikan akhlak bisa menggunakan pengukuran dan penilaian yang memiliki banyak ragamnya, namun tolok ukurnya adalah bukan sekadar angka melainkan kedekatan anak dengan Allah Swt. Menjadi suatu keniscayaan jika pokok pendidikan akhlak anak terpenuhi, maka akan terwujud manusia berakhlak mulia yang insya Allah akan mendapat ridho Allah SWT.